What makes a successful relay start in swimming? - Veiga, S.; Braun, C.; Qiu, X.; Stosic, J.; Fuhrmann, S.; Kibele, A.; Fischer, S. (Sports Biomechanics, 2024)
Despite the mechanical advantage of preparatory movements on the starting block, current evidence questions the start improvements of competitive swimmers with their relay techniques. Therefore, the aim of the present study was to analyse the kinetic and kinematic parameters of a successful relay start. Twenty national- and international-level swimmers performed several relay starts (n = 145) with their preferred technique (short or long-step start) over an instrumented OBS11 starting platform. Trials were classified as successful or non-successful depending on the 10-m times being faster or slower than their individual start. Linear Mixed Models outlined that successful relay starts were characterised (all p < 0.05) by a later (0.04 s) onset of the leg step, a lower (18%) horizontal force during the leg step, and a later (0.03 s) positioning of the hands at the lowest point of the upper-limb backswing. In addition, greater values for the maximal horizontal (12%) and vertical (9%) forces and faster horizontal (4%) and resultant (3%) velocities were detected when driving off the block. These characteristics were also dependent on the relay technique. Unlike individual track starts, swimmers with fast relay starts employed longer preparatory movements on the block to maximise the time of force application and thus the impulse.